The effectiveness of art therapy based on coping cat program on fear of failure in Syrian war-affected children with secondary traumatic stress symptoms - Mohammad Kalthom; Parisa Darouei; Amir Ghamarani (مجله علوم روانشناختی)
Background: Studies have shown that the Syrian war has significantly impacted the mental health of children, leading to increased levels of stress and anxiety. Various studies indicate that stress and anxiety levels can be modified using art therapy and psychological interventions. However, the utilization of art therapy grounded in psychological interventions for addressing the repercussions of war on Syrian children remains underexplored. Aims: This research aimed to investigate the effectiveness of an art therapy intervention based on the coping cat program in reducing the fear of failure in children affected by the Syrian war and experiencing secondary traumatic stress (STS). Methods: The current study utilized a semi-experimental design with pre-test, post-test, and follow-up (3 months) measurements, involving a sample of Syrian children aged 10–12 exposed to the war. From this population, 153 children who had relocated to the city of Salamieh due to the war were assessed using the Secondary Traumatic Stress Scale (Bride et al., 2004). Out of these, 44 children with higher symptom scores were selected, and, based on entry and exit criteria, 20 of them were randomly assigned to two groups of 10 children: the experimental group (Expressive Art Therapy) and the control group. The art therapy intervention sessions used the Art Therapy Based on Coping Cat Program (Kalthom et al., 2023), and data was collected using the Performance Failure Apprehension Inventory (PFAI) questionnaire (Conrow et al., 2002). Data analysis was performed using repeated measures analysis of variance and the SPSS 26 software. Results: The result of this research demonstrated that art therapy based on Coping Cat Program significantly reduced fear of failure and its dimensions (fear of experiencing shame and embarrassment, fear of loss of self-esteem, fear of an unknown future, fear of losing the love of important people, and fear of upsetting important people) in Syrian children (p< 0.05). Conclusion: Based on the obtained results, it can be concluded that art therapy based on Coping Cat Program can reduce the levels of fear of failure and its sub-dimensions in children affected by the war, and it is recommended to replicate the experiment with a larger sample of war-affected children for further validation.